THE USE OF ONLINE BRITISH COUNCIL APP TO IMPROVE INDONESIAN EYL STUDENTS’ VOCABULARY MASTERY - Nadila, Yulita; Widiastuti, Oktavia; Muzammil, Lasim (Universitas Riau Kepulauan, 2025)
All kinds of online games, from the more practical to the more frivolous, sound strange to the general public, particularly to kids. Having said that, this article will focus on the British Council for Kids App, one of many advantages of playing games online. This study aims to examine the impact of using online games developed by the British Council for Kids to enhance English vocabulary on elementary school children. This study employs a descriptive qualitative approach by interviewing three primary school pupils for its data collection. After learning how to use these activities, the participants in this study reported feeling better. They have a strong desire to learn English, particularly the basics, which include vocabulary. This game not only helps with vocabulary but also with listening comprehension and pronouncing words correctly. It's also convenient that the game can be accessed on mobile phones and desktop computers. According to the results of this study, the online game developed by the British Council for Kids can be a fun, engaging, and successful tool for introducing and expanding children's English vocabulary.